2020
DOI: 10.2981/wlb.00623
|View full text |Cite
|
Sign up to set email alerts
|

Inclement weather and American woodcock building collisions during spring migration

Abstract: Weather appears to influence collisions of migratory birds with human‐built structures including buildings, but formal analyses are lacking. In 2018, as part of a two‐year study at 21 buildings in Minneapolis, Minnesota, USA, we observed a large number of American woodcock Scolopax minor collisions during two early spring snowstorms. We describe these events, analyze associations between weather and woodcock collisions during spring 2018, and compare observations to past studies across the woodcock's range. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Although the two bird species that collided most with windows in our study area are migrants, we recorded significantly more collisions during the month of April, congruent with the beginning of the breeding season and the last part of the spring migration. This result agrees with previous studies that have reported more collisions during this season (Gelb & Delacretaz, 2006; Kahle et al, 2016; Loss et al, 2020; Schneider, Barton, Zirkle, Greene, & Newman, 2018). It has been proposed that this pattern could be related to birds having more active behavior, with increased speed of flight, differing dispersal patterns, and behavior related to nest construction and defense (Hager & Craig, 2014; Klem, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Although the two bird species that collided most with windows in our study area are migrants, we recorded significantly more collisions during the month of April, congruent with the beginning of the breeding season and the last part of the spring migration. This result agrees with previous studies that have reported more collisions during this season (Gelb & Delacretaz, 2006; Kahle et al, 2016; Loss et al, 2020; Schneider, Barton, Zirkle, Greene, & Newman, 2018). It has been proposed that this pattern could be related to birds having more active behavior, with increased speed of flight, differing dispersal patterns, and behavior related to nest construction and defense (Hager & Craig, 2014; Klem, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Weather also was likely to contribute to the temporal variation we observed, especially for week-to-week variation in collisions. Weather conditions have been shown to influence building collisions for one species, the American Woodcock ( Scolopax minor ) 56 . Although formal analyses of weather effects on total bird collisions are lacking, weather appears to have contributed to several major bird collision events, including at buildings 45 , 57 , 58 and other types of structures 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Weather conditions such as precipitation, cloud cover, and the presence and/or strength of headwinds or tailwinds—as well as extreme weather events like intense storms—are known to influence the timing and magnitude of bird migration 35 , and are thus likely to influence collision risk. Some of these factors (e.g., low cloud ceilings) may have especially strong effects on nocturnal migrants by exacerbating effects of nocturnal lighting and driving birds into areas of greater collision risk 32 , 56 . When considering the week-to-week variation we observed within seasons, the fine-scale peaks and lulls in collisions may respectively reflect weather conditions that favor or disfavor bird migration (e.g., strong tailwinds or headwinds, respectively) and/or elevate or reduce collision risk for migrating birds (e.g., low cloud ceilings or clear skies, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, ALAN ‘sky glow’ is exacerbated by low clouds and precipitation (Kyba et al., 2015). Studies have linked building collisions with both ALAN (Lao et al., 2020; Winger et al., 2019) and the above types of inclement weather (Loss et al., 2020), suggesting that low average flight altitude, as driven by factors like weather and lighting, may also increase collisions.…”
Section: Discussionmentioning
confidence: 99%